Study of thioglycosylation in ionic liquids - Jianguo Zhang (Beilstein Journal of Organic Chemistry, 2006)
A novel, green chemistry, glycosylation strategy was developed based upon the use of ionic liquids. Research studies demonstrated that thiomethyl glycosides could readily be activated with methyl trifluoromethane sulfonate, using 1-butyl-3-methylimidazolium tetrafluoroborate as a solvent. This green chemistry glycosylation strategy provided disaccharides with typical yields averaging 75%. The ionic liquid solvent could be readily reused for five sequential glycosylation reactions with no impact on product yield.